2015
DOI: 10.1111/tpj.13064
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana isoprenyl diphosphate synthases produce the C25 intermediate geranylfarnesyl diphosphate

Abstract: Isoprenyl diphosphate synthases (IDSs) catalyze some of the most basic steps in terpene biosynthesis by producing the prenyl diphosphate precursors of each of the various terpenoid classes. Most plants investigated have distinct enzymes that produce the short-chain all-trans (E) prenyl diphosphates geranyl diphosphate (GDP, C10 ), farnesyl diphosphate (FDP, C15 ) or geranylgeranyl diphosphate (GGDP, C20 ). In the genome of Arabidopsis thaliana, 15 trans-product-forming IDSs are present. Ten of these have recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 75 publications
4
72
1
Order By: Relevance
“…Kinetic analysis using Lineweaver-Burk plots revealed that the recombinant GFDPS preferred allylic diphosphates as substrates in the order of GGDP = FDP > GDP > DMADP ( Table 2). The kinetic constants for GGDP and IDP were in the same range as those for other IDSs (Schmidt and Gershenzon, 2007;Nagel et al, 2015).…”
Section: Cloning Expression and Characterization Of A Gfdp Synthasesupporting
confidence: 48%
See 4 more Smart Citations
“…Kinetic analysis using Lineweaver-Burk plots revealed that the recombinant GFDPS preferred allylic diphosphates as substrates in the order of GGDP = FDP > GDP > DMADP ( Table 2). The kinetic constants for GGDP and IDP were in the same range as those for other IDSs (Schmidt and Gershenzon, 2007;Nagel et al, 2015).…”
Section: Cloning Expression and Characterization Of A Gfdp Synthasesupporting
confidence: 48%
“…Lc-GFDPS shares 52 to 62% identity with Arabidopsis GFDPSs and GFDPSs from other Brassicaceae plants (Nagel et al, 2015;Wang et al, 2015), but only 33 and 34% identity with M. mazei GFDPS and A. pernix GFDPS, respectively. In Arabidopsis, GFDPS activity is associated with a change in the 5th amino acid in front of the first aspartate-rich motif from Met in GGDPS to Ala or Ser in GFDPS.…”
Section: Gfdp Synthase Provides the Precursor For Sesterterpenoid Formentioning
confidence: 99%
See 3 more Smart Citations